Struktur Populasi Trichogrammatoidea armigera, Parasitoid Telur Helicoverpa armigera, Berdasarkan Analisis RAPD-PCR - Bahagiawati Amir Husin; Damayanti Buchari; Nurindah Nurindah; Habib Rizjaani; Dwinita Wikan Utami; B. Sahari; A. Sari (Jurnal AgroBiogen, 2006)
Population Structure of Trichogrammatoidea armigera,Egg Parasitoid of Helicoverpa armigera Based on RAPDPCRAnalysis. Bahagiawati, Damayanti Buchari, Nurindah,H. Rizjaani, Dwinita W. Utami, B. Sahari, and A.Sari. Genetic structures of Trichogrammatoidea armigera(Hymenoptera: Trichogrammatidae), the egg parasitoid ofHelicoverpa armigera (Lepidoptera: Noctuidae) were studied.Egg masses of H. armigera were collected from fields ofseveral locations in West Java and East Java with differentdistances among them and two distinct cultural practices,i.e., monoculture and polyculture. Genetic relationshipsamong T. armigera populations that emerged from the collectedH. armigera eggs were analysed by the RAPD-PCRtechnique using four oligonucleotide primers. The fourprimers revealed 55 presumptive polymorphic loci that wereused to estimate the population structures. The estimatedvalues of Fixation Index (Fst) was 0.16, indicating that therewas a division of the populations into subpopulations. ThisFst value implied the present of reproductive isolationamong the populations that might be due to their lowmigration rate (1.3 insect per generation). This low migrationrate indicated the present of low level of gene flow amongthe populations. A dendrogram resulted from the NTSYSanalysis indicated that the West Java and East Java populationsof the egg parasitoid had quite wide genetic distances,while within each of the populations there was a subdivisionof minor populations. This finding has an important implicationon the program to release Trichogramma spp. as a biologicalcontrol agent. The release of the parasitoid cannot bedone randomly, because if we pick up a minor population,the starter or the released population will mate with thelocal population and multiply, thus the inundation will fail tocontrol the target pest.